Remote Predictive Mapping 5: Using a Lidar Derived DEM to Test the Influence of Variable Overburden Thickness and Bedrock on Drainage and Basin Morphology - Webster, Tim; Gosse, John; Spooner, Ian; Murphy, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
A 4–m lidar digital elevation model (DEM) provides sufficient resolution to examine the impact of variable till cover on the incision history of multiple small (5 km2) catchments in eastern Canada. The study site was selected because it has homogeneous bedrock geology that dips parallel to the land surface, is tectonically stable, has undergone common base level changes, and has a common ice history, with variable overburden thickness, from thin cover in the west to thick cover in the east. Basin morphometrics were compared for similar-size basins that have variable till cover thicknesses. Basins with thicker till cover are wider and show differences in hypsometries compared to those where till cover is thin. Two basins representing end members of till thickness were measured for stream discharge and water chemistry. Thick till (> 1 m) on the eastern half of North Mountain retards infiltration sufficiently to promote overland flow and accelerate incision relative to areas with thinner till. Till thickness and continuity therefore are expected to impede the achievement of steadiness and may also delay stream power law relationships in larger catchments until till cover has been effectively eroded.